2014
DOI: 10.1124/dmd.113.055095
|View full text |Cite
|
Sign up to set email alerts
|

Common Drugs Inhibit Human Organic Cation Transporter 1 (OCT1)-Mediated Neurotransmitter Uptake

Abstract: The human organic cation transporter 1 (OCT1) is a polyspecific transporter involved in the uptake of positively charged and neutral small molecules in the liver. To date, few endogenous compounds have been identified as OCT1 substrates; more importantly, the effect of drugs on endogenous substrate transport has not been examined. In this study, we established monoamine neurotransmitters as substrates for OCT1, specifically characterizing serotonin transport in human embryonic kidney 293 cells. Kinetic analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 43 publications
4
46
1
Order By: Relevance
“…HEK-OCT1 cells exhibited enhanced verapamil-inhibitable accumulation of dopamine comparatively to HEK-MOCK cells (Fig 5A), thus fully confirming that OCT1 handles dopamine [52]. Allethrin used at 10, 100 or 300 μM was found to significantly inhibit this OCT1-mediated transport of dopamine (Fig 5B); tetramethrin also decreased it, but only when used at 100 or 300 μM (Fig 5B).…”
Section: Resultssupporting
confidence: 60%
“…HEK-OCT1 cells exhibited enhanced verapamil-inhibitable accumulation of dopamine comparatively to HEK-MOCK cells (Fig 5A), thus fully confirming that OCT1 handles dopamine [52]. Allethrin used at 10, 100 or 300 μM was found to significantly inhibit this OCT1-mediated transport of dopamine (Fig 5B); tetramethrin also decreased it, but only when used at 100 or 300 μM (Fig 5B).…”
Section: Resultssupporting
confidence: 60%
“…Localized to the sinusoidal membrane of hepatocytes, OCT1 mediates the hepatic uptake of a diverse array of small positively charged hydrophilic compounds, including many endogenous bioactive amines 1 (e.g., dopamine, histamine, and serotonin). We recently identified OCT1 as a high-capacity transporter of thiamine in the liver and showed that the transporter plays a key role in modulating hepatic energy status and lipid content.…”
Section: ■ Introductionmentioning
confidence: 99%
“…To examine this possibility, we tested successfully some OCT1 inhibitors and found verapamil the most suitable one. We used verapamil in a concentration of 32x the IC 50 for the OCT1 substrate metformin [15], 14 times the IC 50 for serotonin [16], and 6x the IC 50 for tetraethylammonium TEA [17], to achieve a nearly complete inhibition of OCT1-mediated transport. After 5 min incubation of the cell suspensions with verapamil, we repeated the addition of the FC5-208A during the course of the same mass spectrometric experiment as performed in Fig.…”
Section: Resultsmentioning
confidence: 99%